Equal Employment Rights of the Roman Army Administration: An Archetype of Modern Day Human Resource Management - Suvagondha, Thaweesakdhi (European Scientific Journal, ESJ, 2018)
Gaius Marius introduced a new act during his first consulship of the Roman Republic in 107 B.C. with the approval of the Senate. This act allowed him to alter the strategy for managing the Roman army. He permitted every eligible Roman citizen to join the army and thus to pursue the career of a professional soldier. Rome then put soldiers on the payroll. Rome also paid for arms, bodily protection, and other necessities. Marius tasked seasoned soldiers with providing field training to the new recruits on the battlefield. The new recruits learned an important lesson: the bravest was the safest. After expeditions, Marius divided the booty equally among his soldiers as an incentive to encourage victory and reward bravery. These practices stood in stark contrast to the Servian Segregation Decree, which Rome enforced during the reign of King Servius Tullius (578 to 534 B.C.). The Decree prohibited the poorest citizens from becoming Roman soldiers. The drafted soldiers also had to pay for their own arms, bodily protection, and other necessities. At the end of the war, they were discharged to return to their former civilian careers, such as farming and smithing. After the Marius era, the employment rights based on the army administration had evolved and fully developed to cover every step of the Roman soldier employment process: recruitment, enrollment, training and development, employment conditions, performance appraisal, and punishment. This process became one of the Roman army’s key success factors for the next several hundred years. Modern management practitioners should incorporate the Roman army administration process into the legal obligations within the company’s employment policy. The legality of the policy is a result of the adoption of the United Nations Declarations, Conventions, and Covenant into member states’ local laws and regulations. This paper focuses on the documentary research method to analyze and assess the relevant documents.